Synthesis and development of inverse-type nucleoside diarylethene photoswitches - Hendrich, Christoph; Reinschmidt, Martin; Büllmann, Simon; Kolmar, Theresa; Jäschke, Andres (Chemistry - a European journal, 2024)
Nucleosidic diarylethenes (DAEs) have evolved from an emerging class of photochromes into a well-established option for integrating photochromic functionalities into biological systems. However, a comprehensive understanding of how chemical structure influences their photochromic properties remains essential. While structural features, such as an inverse connection between the aryl residues and the ethene bridge, are well-documented for classical DAEs, their application to nucleosidic DAEs has been underexplored. In this study, we address this gap by developing three distinct types of inverse nucleosidic DAEs-semi-inverse thiophenes, semi-inverse uridines and inverse uridines. We successfully synthesized these compounds and conducted comprehensive analyses of their photostationary states, thermal stability, reversibility, and reaction quantum yields. Additionally, we conducted an in-depth comparison of their photochromic properties with those of their normal-type counterparts. Among the synthesized compounds, seven semi-inverse thiophenes exhibited the most promising characteristics. Notably, these compounds demonstrated excellent fatigue resistance, with up to 96 % retention of photochromic activity over 40 switching cycles, surpassing the performance of all comparable nucleosidic DAEs reported to date. These findings hold significant promise for future applications in various fields.